Networks originate in minds: An exploration of trust self-enhancement and network centrality in multiparty systems - Oana C. Fodor; Alina M. Fleștea; Iulian Onija; Petru L. Curșeu (Administrative Sciences, 2018)
Multiparty systems (MPSs) are defined as collaborative task-systems composed of various stakeholders (organizations or their representatives) that deal with complex issues that cannot be addressed by a single group or organization. Our study uses a behavioral simulation in which six stakeholder groups engage in interactions in order to reach a set of agreements with respect to complex educational policies. We use a social network perspective to explore the dynamics of network centrality during intergroup interactions in the simulation and show that trust self-enhancement at the onset of the simulation has a positive impact on the evolution of network centrality throughout the simulation. Our results have important implications for the social networks dynamics in MPSs and point towards the benefit of using social network analytics as exploration and/or facilitating tools in MPSs.
Keywords: 350; social networks; multiparty systems; trust; centrality